Enhancing Methanol Production from Syngas through Heat Exchanger Modification and Vapour Distillate Flow Optimization - Diana Dwi Sri Astuti; Azmi Mu'amar; Agnes Theresia Petra S; Adita Maizalfania; Azifa Rusyda Dewi; Syafirah Nurrahim (Journal of Chemical Engineering Research Progress, 2025)
Methanol production from syngas represents a promising route to strengthen energy independence and reduce reliance on imports. Conventional processes, however, are constrained by low per-pass conversion and unstable reactor inlet conditions, which limit efficiency and accelerate catalyst deactivation. This study investigates process modifications, focusing on two key strategies: the addition of a heat exchanger to stabilize and elevate reactor inlet temperatures, and the optimization of vapor distillate flow in the distillation column to enhance product purity. The modified process achieved a substantial improvement in methanol conversion, rising from 28.34% in the base configuration to 98.70%, while product purity increased from 97.68% to 98.95%. The heat exchanger ensured better thermal conditioning of recycle streams, reducing temperature fluctuations and improving reaction stability, whereas distillate flow optimization enhanced separation efficiency by balancing vapor and liquid reflux. These results demonstrate that targeted retrofitting of existing plants can deliver significant gains in efficiency, stability, and sustainability without the need for new construction. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).